SUFI PHILOSOPHICAL CONCEPTS IN MAQOM MUSIC - Davronova Aziza Mirzoyevna (Western European Studies, 2025)
This article explores the historical and philosophical connections between maqom and Sufism, examining the educational and spiritual significance of music and mystical thought before and after the advent of Islam. It analyzes the spiritual and philosophical unity between maqom melodies and Sufi teachings, examples of maqoms resembling zikr, and the transformative influence of music in spiritual development
Keywords: Maqom; Ushshoq; Girya